Enhanced Expression of miR-34c in Peripheral Plasma Associated with Diabetic Foot Ulcer in Type 2 Diabetes Patients - Wu T (Dove Medical Press, 2021)
Tingting Wu,* Dandan Xie,* Xiaotong Zhao, Murong Xu, Li Luo, Datong Deng, Mingwei Chen Department of Endocrinology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mingwei ChenDepartment of Endocrinology, The First Affiliated Hospital of Anhui Medical University, No. 218 Jixi Road, Hefei, Anhui, 230032, People’s Republic of ChinaEmail chmw1@163.comObjective: To explore the correlation between the expression of miR-34c in peripheral blood of patients with type 2 diabetes mellitus (T2DM) and the onset of diabetic foot ulcer (DFU) and diabetic foot osteomyelitis (DFO).Methods: Sixty newly diagnosed patients with T2DM without DFU (T2DM group), 112 T2DM patients with DFU (DFU group) and 60 controls with normal glucose tolerance (NC group). The DFU group patients were subdivided into DFO (n=64) and NDFO (n=48) groups. Quantitative real-time PCR (qRT-PCR) method was used to determine miR-34c expression levels in the peripheral blood of subjects to analyze the clinical characteristics of DFU and DFO risk factors.Results: MiR-34c expression level in the T2DM group was marked higher than the NC group [2.99 (1.45– 6.22) vs 1.01 (0.89– 1.52)] (P < 0.05). However, the expression level of miR-34c in the DFU group was significantly higher than the T2DM group [9.65 (6.15– 18.63) vs 2.99 (1.45– 6.22)] (P < 0.01). Compared with the NDFO group, the expression level of miR-34c in the DFO group was also obviously increased [13.46 (8.89– 19.11) vs 6.02 (5.93– 14.72)] (P < 0.01). The expression level of miR-34c in DFU patients was positively correlated with the amputation rate of foot ulcers (P=0.030) and was negatively correlated with the healing rate of foot ulcers after eight weeks (P=0.025). Multifactorial logistic regression analysis showed that increased expression of miR-34c was an independent risk factor for DFU and DFO (ORDFU=3.47, ORDFO=4.25, P < 0.01). Meanwhile, the ROC curve analysis indicated that the AUC of miR-34c for the diagnosis of DFU and DFO was 0.803 and 0.904, the optimum sensitivity being was 100% and 98.7%, the optimum specificity was 98.4% and 98.4%, respectively.Conclusion: The increased expression of miR-34c in peripheral blood of T2DM patients is closely related to the occurrence, development and prognosis of DFU and DFO.Keywords: type 2 diabetes, diabetic foot, diabetic foot osteomyelitis, miRNAs